A new landhopper, Manawataawhiorchestia uruone gen. nov., sp. nov. (Amphipoda: Talitroidea: Talitridae) from Manawatāwhi/Three Kings Islands, New Zealand - Myers, Alan A.; Ball, Olivier J.-P.; Shepherd, Lara D. (Zootaxa, 2025)
A new genus and species of landhopper in the family Talitridae, Manawataawhiorchestia uruone gen. nov., sp. nov., is here described from the Three Kings Islands, New Zealand. Until recently, all native landhoppers in New Zealand had been attributed to the family Makawidae. Following the transferral of Dallwitzia simularis (Hurley, 1957) to the Talitridae Manawataawhiorchestia uruone gen. nov., sp. nov. becomes the second species of talitrid landhopper identified from New Zealand. All other New Zealand species in the family Talitridae have been classified as beachhoppers and sandhoppers.